Numerical Optimization of Microperforated panel Absorbers: The Impact of Series-Parallel Configuration, Air Gap, and Porous Materials on the Sound Absorption Bandwidth - Mohammad Javad SheikhMozafari; Zahra Hashemi; Ali Mohsenian (بهداشت و ایمنی کار)
Introduction: Micro-perforated panel (MPP) absorbers are emerging as next-generation absorbers due to their considerable advantages. However, their main drawback compared to other absorbers is their limited bandwidth. This study aims to investigate methods for enhancing the bandwidth of an MPP in the frequency range of 1 to 1500 Hz through simulation using the Finite Element Analysis (FEA) in COMSOL software. Material and Methods: The modeling was conducted using FEA in COMSOL version 5.3a. To increase the bandwidth, techniques such as series-parallel configurations, symmetrical and asymmetrical air gap depths, and the incorporation of two porous absorbing materials in symmetric and asymmetric air gap layers were employed. In the initial phase, the best configuration was selected and retained for the subsequent stages. Results: The optimal arrangement involved two upper MPPs having larger holes and a lower perforation percentage compared to the two lower MPPs. It was also found that increasing the depth difference between the air layers of the upper and lower MPPs led to a greater increase in bandwidth than when they were closer together. Furthermore, the use of fibrous porous materials in one of the layers resulted in a reduction of resonance peak while enhancing the bandwidth. Conclusion: MPP absorbers exhibit diverse behaviors due to their Helmholtz structure and parametric design. If their constituent parameters are tailored to match the acoustic characteristics of the target sound, they achieve optimal efficiency. Additionally, employing numerical methods such as FEA serves as a suitable alternative to more costly laboratory methods.